Pemberdayaan Petani Desa Wirosari melalui Pelatihan Pupuk Organik dari Limbah Kotoran Kambing - Tri Wulaningsih; Berliani Kusuma Rahma Darajat; Malika Ayu Sholihah; Sita Nurmasitah; Danang Hasto Wibowo (Perkumpulan Kualitama Edukatika Indonesia, 2025)
Agricultural production in rural areas produces large amounts of organic waste, such as straw, weeds, and livestock manure, which is often not optimally utilized, causing environmental pollution. One solution that can be implemented is to process this waste into solid organic fertilizer that is useful for improving soil fertility. The Integrated Intensive and Applied Movement (GIAT) 12 Program of Semarang State University conducted training on making organic fertilizer from goat manure in Wirosari Village, Patean District, Kendal Regency, involving the Women Farmers Group as partners. This activity was carried out through socialization, counseling, technical practice, and participatory evaluation. The results of the training showed a significant increase in community knowledge, from only 40% of participants understanding the concept of organic fertilizer before the activity to 100% after the activity. In addition, participants were able to practice making solid organic fertilizer using goat manure, molasses, and Effective Microorganisms 4 (EM4) with a fermentation time of approximately two weeks. The positive impacts of this activity include improving community skills, strengthening the value of mutual cooperation, reducing dependence on chemical fertilizers, and opening up new economic opportunities through independent organic fertilizer production. For the sustainability of the program, support is needed in the form of facilities, continued mentoring, and development of the product value chain so that the social, economic, and environmental benefits can continue to be felt by the community.